Syphilis in pregnancy and congenital syphilis: women's experiences from the perspective of symbolic interactionism - Jéssica Batistela Vicente; Gabriel Zanin Sanguino; Maria Regina Pontes Luz Riccioppo; Maiara Rodrigues dos Santos; Maria Cândida de Carvalho Furtado (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to understand the meanings attributed by women to the diagnosis and treatment of syphilis and congenital syphilis, and to outpatient follow-up of their children. Methods: this is a qualitative study conducted with 30 mothers of children with congenital syphilis using audio-recorded semi-structured interviews, which were submitted to inductive thematic analysis. Symbolic interactionism was the theoretical framework considered in this study. Results: two themes were identified, showing the maternal diagnosis involved shock, guilt, and fear of social exclusion, in addition to frustration due to failure to prevent vertical transmission. Moreover, the painful clinical procedures for the child's treatment enhanced maternal guilt, and the symbolic process of re-signification of the disease/treatment took place with the child's healing. Final Considerations: understanding the intersubjective aspects involved in this experience helps nurses rethink their care practice and contributes to their critical role in the context of syphilis.